Rogue access point detection and tracking in UTAR campus - Lee, Chiew Min (2024)
In the contemporary age of ubiquitous wireless networks, the issue of rogue access points (RAPs) has emerged as a paramount apprehension in the realm of network security. The primary objective of this project is to address the challenge of detecting and monitoring unauthorized access points, commonly referred to as rogue access points (RAPs), within higher education institutions. The specific focus of this endeavour is to enhance the security protocols at University Tunku Abdul Rahman (UTAR). The primary aim of this study is to present a very efficient methodology for detecting rogue access points (RAPs) and a resilient signal strength that can improve the precision of the system. The study begins by doing a thorough analysis of network security vulnerabilities. This is followed by a detailed review of relevant literature on methods for detecting rogue access points (RAPs). The main aim of the proposed a signal strength to calculate an approximate distance and mitigate occurrences of unauthorized network access, consequently reducing the resulting financial and reputational implications. The project entails the development of a holistic system design that integrates the technical aspects of the algorithm alongside the hardware specifications. The system functions by evaluating the intensity of the received signal to detect rouge access points (RAPs), and subsequently use signal strength to calculate the distance and approximate location. The testing and evaluation activities will be conducted within the campus premises of UTAR. The provided content serves as a valuable resource for additional inquiries in the fields of network security and the identification of rogue access points (RAPs). The program demonstrates a commitment to ethical principles by strictly adhering to regulations for data protection.